HIDDEN CURRICULUM IN A SUBURBAN HIGH SCHOOL: EXPLORING GENDER NORMS AND EXPECTATIONS FOR STUDENT PARTICIPATION - Md. Zahidul Islam; Md. Minhajul Arefin; Md. Sobur Hossain; Nishat Tasnim; Md Jayedul Haque; Tanha Begum (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2025)
Hidden curriculum refers to the beliefs, attitudes, and conduct of students in the classroom, apart from the explicit subject taught in textbooks. This paper has discussed how student participation at Amin Bazar Ideal School in Amin Bazar, Dhaka, has influenced and changed traditional gender norms and expectations. This was motivated by concerns that any subtle support of societal norms and expectations regarding classroom communications, teacher actions, and institutional policies symbolizes conventional gender roles. A quantitative approach was employed to collect data through questionnaires, interviews, and classroom observations to examine the influence of gender on student participation in academic and extracurricular activities. The findings indicated that the hidden curriculum significantly supported conventional gender roles, with girls being directed toward submissive roles and boys being encouraged toward assertiveness and leadership. Data analysis was conducted using SPSS software. The data present hidden biases that need to be addressed to ensure gender equality and a supportive and inclusive educational environment. The figures on student involvement illustrate that 55% of the respondents favor excellent engagement, 11% strongly agree, 44% agree, 38% are undecided, and 7% disagree. Classroom gender participation has no appreciable correlation with socioeconomic level or gender identity according to the Pearson Correlation Coefficient of 0.120.